Microarray analysis of gene regulation by oxygen, nitrate, nitrite, FNR, NarL and NarP during anaerobic growth of Escherichia coli: new insights into microbial physiology. (20th January 2006) - Overton, T.W.; Griffiths, L.; Patel, M.D.; Hobman, J.L.; Penn, C.W.; Cole, J.A.; Constantinidou, C.
Abstract : RNA was isolated from cultures of Escherichia coli strain MG1655 and derivatives defective in fnr, narXL, or narXL with narP, during aerobic growth, or anaerobic growth in the presence or absence of nitrate or nitrite, in non-repressing media in which both strain MG1655 and an fnr deletion mutant grew at similar rates. Glycerol was used as the non-repressing carbon source and both trimethylamine- N -oxide and fumarate were added as terminal electron acceptors. Microarray data supplemented with bioinformatic data revealed that the FNR (fumarate and nitrate reductase regulator) regulon includes at least 104, and possibly as many as 115, operons, 68 of which are activated and 36 are repressed during anaerobic growth. A total of 51 operons were directly or indirectly activated by NarL in response to nitrate; a further 41 operons were repressed. Four subgroups of genes implicated in management of reactive nitrogen compounds, NO and products of NO metabolism, were identified; they included proteins of previously unknown function. Global repression by the nitrate- and nitrite-responsive two-component system, NarQ-NarP, was shown for the first time. In contrast with the frdABCD, aspA and ansB operons that are repressed only by NarL, the dcuB - fumB operon was among 37 operons that are repressed by NarP.